Respuesta :

Answer:

The pair of solutions are [tex](-2,-1) \ and\ (3,14)[/tex]

Step-by-step explanation:

[tex]1)y=x^2+2x-1\\2)y-3x=5[/tex]

Solving for [tex]y[/tex] in equation 2.

[tex]y-3x=5[/tex]

Adding [tex]3x[/tex] both sides.

[tex]y-3x+3x=5+3x[/tex]

[tex]y=5+3x[/tex]

Substituting value of [tex]y[/tex] in equation 1.

[tex]5+3x=x^2+2x-1\\[/tex]

Simplifying it further. Subtracting [tex]5[/tex] from both sides.

[tex]5+3x-5=x^2+2x-1-5\\[/tex]

[tex]3x=x^2+2x-6\\[/tex]

Subtracting [tex]3x[/tex] both sides.

[tex]3x-3x=x^2+2x-6-3x\\[/tex]

[tex]0=x^2-x-6\\[/tex]

Now we have a quadratic equation to solve.

[tex]x^2-x-6=0[/tex]

Solving quadratic by factor method.

Splitting the middle term into two terms [tex]mx \ and\ nx[/tex] such that [tex]mx+nx=-x \ and (mx)(nx)=-6x^2[/tex]

By factoring 6 we can get the terms.

[tex]mx=-2x \ and\ nx=3x[/tex] As we know [tex][2x-3x=-x \ and\ (2x)(-3x)=-6x^2][/tex]

So, the equation would be

[tex]x^2+2x-3x-6=0[/tex]

Now, we factor in pairs.

Taking [tex]x[/tex] as common factor from first two terms and taking [tex]-3[/tex] common from last two terms.

[tex]x(x+2)-3(x+2)=0[/tex]

Taking [tex](x+2)[/tex] as common factor from the whole.

[tex](x+2)(x-3)=0[/tex]

The roots can be written as:

[tex]x+2=0 \ and\ x-3=0[/tex]

Solving for [tex]x[/tex] from the above we get

[tex]x=-2 \ and\ x=3[/tex]

Plugging the values of [tex]x[/tex] in the equation [tex]y=5+3x[/tex]

When [tex]x=-2[/tex]

[tex]y=5+3(-2)[/tex]

[tex]y=5-6[/tex]

[tex]y=-1[/tex]

So [tex](-2,-1)[/tex] is one solution.

When [tex]x=3[/tex]

[tex]y=5+3(3)[/tex]

[tex]y=5+9[/tex]

[tex]y=14[/tex]

So [tex](3,14)[/tex] is another solution.